2015
DOI: 10.1016/j.ssci.2014.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to OHS interventions in Small and Medium-sized Enterprises

Abstract: a b s t r a c tBarriers to OHS interventions are factors that hinder proper design, implementation and evaluation. An analysis of the barriers is crucial for understanding intervention effectiveness and improving the way in which design, implementation and evaluation of interventions are carried out. However, there is little consensus on how barriers should be understood, how important they are in different contexts, and how they can hinder OHS interventions. This exploratory study based on interviews with 58 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 52 publications
5
84
0
Order By: Relevance
“…SMEs do not have at their disposal OHS measurement tools and methods that are adapted to their work environments and scales of operation [8,24]. Among the factors cited to explain the unavailability of tools suitable for measuring their maturity level are insufficient economic, technological and human resources, the adopted managerial mode and efforts oriented towards productivity and quality to the detriment of OHS [26].…”
Section: Ohs Risk Management Tools and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…SMEs do not have at their disposal OHS measurement tools and methods that are adapted to their work environments and scales of operation [8,24]. Among the factors cited to explain the unavailability of tools suitable for measuring their maturity level are insufficient economic, technological and human resources, the adopted managerial mode and efforts oriented towards productivity and quality to the detriment of OHS [26].…”
Section: Ohs Risk Management Tools and Methodsmentioning
confidence: 99%
“…Prevention by design Not specified [83][84][85] Commitment of management Not specified [24,59,79] Worker commitment and participation -Percent response to questionnaires [24,59,78,86] OHS-related behaviour -Number of observations of unsafe or deviant actions [78,87] Compliance with OHS guidelines or regulations -Number of penalties for non-compliance [8,23,40,54,88] OHS inspection -Number of inspections carried out [25,40,79,86] Equipment and preventive maintenance Not specified [25,79] Work setting and situations potentially at risk Not specified [7,8,20,24,79] Evaluation of proactive indicators Not specified [74,79,86] Technology -Degree of integration of technology into the processes [33,89] Budget -The amount allotted to OHS [33,40,59] Workload -Evaluation of workload [90] …”
Section: Proactive Indicator Examples Of Measurement Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Masi & Cagno (2015) proposed a framework of 27 barriers to OHSMS intervention in small companies and implemented it to owners/managers of small European manufacturers; the top 10 barriers include the follwing: regulation (rigorous legislation and bureaucracy); resources (inadequate dedication of time and inadequate dedication of financial resources); and information (missing or ineffective communication, missing or ineffective information, lack of knowledge of critical situations of the company by employees, lack of technical support from the authorities, and lack of guidelines). Cagno et al (2016) found that external consultant support, availability of knowledge of effective interventions, collaborations with business associations and collaboration with other stakeholders are essential for OHSMS implementation.…”
Section: Ohsms In Small Enterprisesmentioning
confidence: 99%